2008
DOI: 10.1159/000155210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Isolated Histological Components of Wilms Tumor Implicates a Common Role for the Wnt Signaling Pathway in Kidney and Tumor Development

Abstract: Wilms tumor (WT), a tumor composed of three histological components – blastema (BL), epithelia and stroma – is considered an appropriate model system to study the biological relationship between differentiation and tumorigenesis. To investigate molecular associations between nephrogenesis and WT, the gene expression pattern of individual cellular components was analyzed, using a customized platform containing 4,608 genes. WT gene expression patterns were compared to genes regulated during kidney differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 65 publications
0
30
0
3
Order By: Relevance
“…We and others have demonstrated that nephrogenesis and Wilms tumorigenesis share gene expression regulation patterns32333435. Furthermore, repression of miRNA maturation through inhibition of DROSHA and DICER1 expression impairs accurate kidney differentiation363738 and promotes tumorigenesis in several cell lines39.…”
Section: Discussionmentioning
confidence: 98%
“…We and others have demonstrated that nephrogenesis and Wilms tumorigenesis share gene expression regulation patterns32333435. Furthermore, repression of miRNA maturation through inhibition of DROSHA and DICER1 expression impairs accurate kidney differentiation363738 and promotes tumorigenesis in several cell lines39.…”
Section: Discussionmentioning
confidence: 98%
“…Although the etiology of embryonal tumors has not been fully clarified, evidence supports the hypothesis of failure in the normal process of differentiation during fetal or postnatal development [3,24]. Several studies have investigated the role of environmental factors during pregnancy that could be causally related to HB development [5], including pre-eclampsia [25], maternal overweight condition during pregnancy [26,27], and treatment for infertility [26].…”
Section: Environmental and Genetic Risk Factorsmentioning
confidence: 99%
“…4, 5 More recently, we have provided evidence that, among the three histological WT components, blastemal cells display a gene expression profile similar to that found in the initial stages of nephrogenesis, suggesting that the blastemal component, and not the whole tumor, preserves the molecular events involved in WT onset. 6 …”
mentioning
confidence: 99%